Pengaruh Harga Dan Promosi Terhadap Keputusan Pembelian Konsumen Pada Depo Air Minum Biru Meruyung Depok - Nadila, Dina Rieska; Rosento Rosento (Lembaga Pengembangan Kinerja Dosen, 2024)
The current business environment has become increasingly competitive Due to this competitive market, every company must constantly be vigilant of the competition in its work environment Every business actor must be able to implement successful marketing tactics and continuously improve these marketing strategies in order to compete in a strong and tight market Affordable prices and attractive promotions can attract consumers and enhance purchasing decisions for a product to be marketed This research is conducted with the aim of understanding the impact of Price and Promotion on purchasing decisions. The method used in this research is quantitative statistical research method, using a research instrument in the form of a questionnaire distributed through the researcher's social media, and utilizing SPSS version 25. Based on the questionnaire results from 98 respondents, it can be concluded that affordable and appropriate prices, as well as attractive promotions, significantly influence consumer purchasing decisions.